NATURAL PROTECTIVE FACTORS IN THERAPY OF INFLAMMATORY PHARYNX AND LYMPHOID RING DISEASES - S. A. Artyushkin; N. V. Eremina (Медицинский совет, 2017)
Pharynx and pharyngeal lymphadenoid elements possess  diverse protective mechanisms, however, are often involved in the inflammatory process. Lysozyme is important natural factor in the maintenance of normal pharyngeal microbiome. The article presents the data about the efficient use of factors of natural protection of lysozyme and pyridoxine for the treatment of acute inflammatory diseases with lesions of the mucous membrane of the pharynx and lymphadenoid pharyngeal ring.